Розробка методу та програми з контекстним пошуком в інтернеті - Редька, О. С. (ХНУРЕ, 2019)
The work is devoted to solving the problem of contextual search. Methods for identifying keywords that allow searching information according to the query are developed. They consist in the analysis and processing of a search query, as well as information retrieval, based on this query. The methods are based on obtaining an existing query as a string, parsing it, and searching for information according to the query. The developed methods allow finding appropriate matches for the further search of the information on the Internet.